School Communication Systems - Ion Negrila (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Communication has always been a main component of education, an indispensable support for the education system. Receptive to human communication development, the timeless school practice has never stopped to wisely integrate and absorb the various verbal and non-verbal forms and means in its procedural structures. This is today more obvious than ever, in a society of knowledge and globalized communication, when the act of communication is applied effectively in all domains of inter-personal activities and human social life. A major role is played today in this context by the powerful technological communication tools, with major implications in the development of the educational system.